Luminescent AIE Dots for Anticancer Photodynamic Therapy - He, Zhenyan; Tian, Sidan; Gao, Yuting; Meng, Fanling; Luo, Liang (Frontiers in Chemistry, 2021)
Photodynamic therapy (PDT) is an emerging effective strategy for cancer treatment. Compared with conventional cancer therapies such as surgery, chemotherapy, and radiotherapy, PDT has shown great promise as next-generation cancer therapeutic strategy owing to its many advantages, such as noninvasiveness, negligible observed drug resistance, localized treatment, and few side effects. One of the key elements in photodynamic therapy is the photosensitizer (PS), which converts photons into active cytotoxic species, namely reactive oxygen species (ROS). An ideal PS for photodynamic therapy requires the efficient generation of ROS, high stability against photo bleaching, and robust performance in different environments and concentrations. PSs with aggregation-induced emission (AIE) characteristics has drawn significant attention, in that they can overcome the aggregation caused quenching effect that is commonly seen in the case of fluorescence dyes, and provide excellent performance at high concentrations or in condensed state. Moreover, organic nanomaterials with aggregation-induced emission characteristics, or AIE dots, have played an increasingly significant role in assisting PDT based on its excellent ROS generation efficiency and simultaneous imaging feature. This review summarizes the recent advances on the molecular design of AIE PSs and AIE dots-based probes, as well as their emerging applications for enhanced anticancer PDT theranostics.